2019
DOI: 10.1103/physrevapplied.11.014024
|View full text |Cite
|
Sign up to set email alerts
|

Time-Varying Reactive Elements for Extreme Accumulation of Electromagnetic Energy

Abstract: Accumulation of energy by reactive elements is limited by the amplitude of time-harmonic external sources. In the steady-state regime, all incident power is fully reflected back to the external source, and the stored energy does not increase in time, although the external source continuously supplies energy. Here we show that this limitation can be removed if the reactive element is varying in time, properly modulated by an additional active but lossless device. We show that such time-varying lossless loads of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(70 citation statements)
references
References 20 publications
2
66
0
Order By: Relevance
“…The three primed variables ω e , v ± j and j in (33) and (35) may be converted to their unprimed counterparts using respectively ω e = γω e (Eq. (26)), the equation for v ± j in (14), and the length contraction formula…”
Section: Phase Shiftmentioning
confidence: 99%
See 1 more Smart Citation
“…The three primed variables ω e , v ± j and j in (33) and (35) may be converted to their unprimed counterparts using respectively ω e = γω e (Eq. (26)), the equation for v ± j in (14), and the length contraction formula…”
Section: Phase Shiftmentioning
confidence: 99%
“…Time crystals were first studied in the 1960s under the form of temporally modulated 1D structures, whose controlled instabilities led to parametric amplifiers [5,6] and whose asymmetric frequency transitions led to nonreciprocal devices [7,8]. Such time crystals have recently experienced a regain of interest [9][10][11], and more generally time-varying structures [12][13][14]. Moreover, the concept of spontaneous time crystals, which are time crystals produced by a nonperiodic stimulus, was introduced as a new state of matter in [15].…”
Section: Introductionmentioning
confidence: 99%
“…This creates a new paradigm for designing dynamic metasurfaces with 2π phase span and uniform amplitude. Furthermore, time‐modulated metasurfaces give rise to several exotic space‐time scattering phenomena and can be envisioned for a variety of novel applications such as magnetless nonreciprocal components, Doppler cloaking and illusion, pulse shaping, extreme energy accumulation, and localization of light . Development of all‐dielectric time‐modulated metasurfaces is of particular interest as they can enable directional harmonic generation and manipulation in transmission mode by establishing a Huygens' operation regime, eliminating the bidirectionality of harmonics generated by time‐modulated metasurfaces with single isolated resonances.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Ref. [37], it is shown that properly modulating inductive load, reflections from the load can be completely eliminated.…”
Section: Circuit Analogymentioning
confidence: 99%